SELF REGULATION DAN PSYCHOLOGICAL WELL BEING DENGAN FEAR OF MISSING OUT (FoMO) PADA USIA EMERGING ADULTHOOD - Denisa, D. Annisah Dwi Farhani; Wigati, Denok; Mufidah, Wardatul; Nursanti, Erma (IDEA: Jurnal Psikologi, 2024)
Abstract This study aims to determine the relationship between self-regulation and psychological well-being with fear of missing out at the age of emerging adulthood. This study involved 104 samples of individuals who were in the emerging adulthood period with an age range of 18 to 29 years. The data collection technique was carried out online via google form using a purposive random sampling technique. Based on the results of the Spearman Rho Non-Parametric test analysis, the correlation coefficient value between self-regulation and fear of missing out was obtained at -0.331 and sig. or p of 0.001 (p <0.05). This shows that there is a negative relationship between self-regulation and fear of missing out at the age of emerging adulthood. Furthermore, the correlation coefficient value between psychological well-being and fear of missing out is -0.449 and sig. or p of 0.000 (p <0.05). This shows that there is a significant negative relationship between psychological well-being and fear of missing out at the age of emerging adulthood. Keywords: Self-regulation; Psychological well-being; Fear of missing out; Emerging adulthood period Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara self regulation dan psychological well being dengan fear of missing out pada usia emerging adulthood. Penelitian ini melibatkan 104 sampel individu yang berada pada masa emerging adulthood dengan rentang usia 18 sampai 29 tahun. Teknik pengambilan data dilakukan secara online melalui google form dengan menggunakan teknik purposive random sampling. Berdasarkan dari hasil analisis uji Non Parametrik Spearman Rho, maka diperoleh nilai koefisien korelasi antara self regulation dengan fear of missing out sebesar -0.331 dan sig. atau p sebesar 0,001 (p < 0,05). Hal ini menunjukkan bahwa terdapat hubungan negatif antara self regulation dengan fear of missing out pada usia emerging adulthood. Selanjutnya nilai koefisien korelasi antara psychological well being dengan fear of missing out sebesar -0.449 dan sig. atau p sebesar 0,000 (p < 0,05). Hal ini menunjukkan bahwa terdapat hubungan negatif yang signifikan antara psychological well being dengan fear of missing out pada usia emerging adulthood. Kata kunci: Fear of Missing Out; Masa Emerging Adulthood; Psychological Well Being; Self Regulation